Analysis on Machine Learning Techniques - Parvathavardhini, S; Manju, S (International Journal of Computer Sciences and Engineering, 2025)
Machine learning is the self-driven technology. It is the science of getting computers to act without being explicitly programmed. Machine learning refers to self-improving algorithms, explores the study and construction of algorithms that can learn from and make predictions on data. These are predefined processes conforming to specific rules, performed by a computer can be applied to any learning task and it is flexible and it don’t need a programmer or human expert.Machine learning algorithms are common in web applications that we use every day and have a growing relevance to enterprise applications. Two of the most widely adopted machine learning methods are supervised learning and unsupervised learning. While many machine learning algorithms have been around for a long time, the ability to automatically apply complex mathematical calculations to big data – over and over, faster and faster is a recent development.